2002
DOI: 10.1128/jvi.76.24.12917-12924.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Binding Site of Latency-Associated Nuclear Antigen of Kaposi's Sarcoma-Associated Herpesvirus Is Essential for Persistent Episome Maintenance and Is Functionally Replaced by Histone H1

Abstract: Latency-associated nuclear antigen 1 (LANA1) of Kaposi's sarcoma-associated herpesvirus (KSHV; human herpesvirus 8) persistently maintains a plasmid containing the KSHV latent origin of replication (oriP) as a closed circular episome in dividing cells. In this study, we investigated the involvement of chromosome binding activity of LANA1 in persistent episome maintenance. Deletion of the N-terminal 22 amino acids of LANA1 (⌬N-LANA) inhibited the interaction with mitotic chromosomes in a human cell line, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 26 publications
4
78
0
Order By: Relevance
“…At least two other viruses, Kaposi's sarcomaassociated herpesvirus (KSHV, human herpesvirus 8) and bovine papillomavirus-1, are known to attach to host mitotic chromosomes (reviewed by Botchan, 2004). Among these, KSHV encodes latency-associated nuclear antigen (LANA), which is a functional counterpart of EBNA1 in EBV (Ballestas et al, 1999;Barbera et al, 2006;Shinohara et al, 2002). Previous studies demonstrated that the LANA colocalizes with KSHV genomes on mitotic chromosomes (Ballestas et al, 1999) and occasionally exhibits symmetrical localization on sister chromatids of mitotic chromosomes (Szekely et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…At least two other viruses, Kaposi's sarcomaassociated herpesvirus (KSHV, human herpesvirus 8) and bovine papillomavirus-1, are known to attach to host mitotic chromosomes (reviewed by Botchan, 2004). Among these, KSHV encodes latency-associated nuclear antigen (LANA), which is a functional counterpart of EBNA1 in EBV (Ballestas et al, 1999;Barbera et al, 2006;Shinohara et al, 2002). Previous studies demonstrated that the LANA colocalizes with KSHV genomes on mitotic chromosomes (Ballestas et al, 1999) and occasionally exhibits symmetrical localization on sister chromatids of mitotic chromosomes (Szekely et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of papillomavirus E2, EBNA-1 associates with host chromosomes (45), and it has been suggested that the action of the FR in retaining the plasmid involves the viral genome hitchhiking on the host chromosome via EBNA-1. It seems likely that KSHV has evolved a similar chromosome-tethering mechanism for its persistence in host cells (5,14,49,59) and that LANA1 is responsible not only for the stable maintenance but also for the replication of KSHV TRcontaining plasmids (26,28,42). In a transient-replication assay using a panel of LANA1 deletion mutants, the minimal domain of LANA1 able to support the replication of a TRcontaining plasmid was identified as LANA1 ⌬23-950, which contains the N-terminal CBS in addition to the C-terminal DNA-binding and dimerization domain (Lim et al, submitted).…”
Section: Vol 78 2004 Notes 7253mentioning
confidence: 99%
“…Its C terminus binds to sequences within the TRs located at both ends of the KSHV genome and represses TR-dependent transcription (6,15,24,42). As expected from the chromosome-tethering model, the LANA1 CBS is necessary for long-term replication of a KSHV TR-containing plasmid (59). In addition, we and others have shown that LANA1 is required for the transient replication of KSHV TR-containing plasmids, indicating that it may play an essential role not only in plasmid maintenance but also in DNA replication from the KSHV TR (26,28,42).…”
mentioning
confidence: 99%
“…Recombinant KSHV with LANA deleted as well as LANA transcript depletion by shRNA reduced the number of KSHV genomic copies, demonstrating that tethering is important for long-term persistence (26,74). LANA has been shown to bind to cellular proteins to support tethering and replication of the KSHV genome (7,16,40,63,71). In order to identify cellular proteins associated with LANA when LANA is bound to its cognate sequence, we performed an LBS affinity binding assay (71).…”
Section: Host Cellular Protein Binds To Multimerized Lbs Affinity Colmentioning
confidence: 99%
“…Later studies mapped the domains of LANA important for tethering to host chromosomes (5,6,17). LANA associates with human chromatin through the amino-terminal domain and remains attached during all of the phases of the cell cycle (7,54,63). LANA tethers the KSHV genome to host chromosomes through binding at the terminal repeats (TRs) of the KSHV genome (62).…”
mentioning
confidence: 99%